Local indigenous strategy to rehabilitate and conserve mangrove ecosystem in the southeastern Gulf of Kupang, East Nusa Tenggara, Indonesia - RONGGO SADONO; DJOKO SOEPRIJADI; ARI SUSANTI; Jeriels Matatula; EKO PUJIONO; FAHMI IDRIS; PANDU YUDHA ADI PUTRA WIRABUANA (Society for Indonesian Biodiversity, 2020)
Abstract. Sadono R, Soeprijadi D, Susanti A, Matatula J, Pujiono E, Idris F, Wirabuana PYAP. 2020. Local indigenous strategy to rehabilitate and conserve mangrove ecosystem in the southeastern Gulf of Kupang, East Nusa Tenggara, Indonesia. Biodiversitas 21: 1250-1257.  The existence of local communities around mangrove ecosystems plays essential role to support the effort of conservation programs in this area. This study is aimed to investigate a set of situation faced by local communities in the southeastern Gulf of Kupang (SGK), East Nusa Tenggara Province which led to the rehabilitation of once degraded mangrove forests in SGK and the strategies to conserve the recovered mangrove forests. A case study approach was developed using purposive sampling to collect information regarding the historical situation of mangrove forests in SGK. Further, remote sensing method using multi-temporal observation data was used to investigate the changes in mangrove cover from 1994 to 2019. This study revealed that a series of situations became the fundamental of the success in retaining the existence of mangrove ecosystems in SGK. First, the negative impacts of mangrove degradation affected the communities badly in relation to their livelihoods in fisheries and marine sector as well as other environmental services. Then, this situation led to the emergent of a local champion to initiate mangrove rehabilitation efforts which firstly did not get attention from most of the communities. After some initial successes, the efforts of the local champion was then followed by other members of communities, triggering a bigger scale of mangrove rehabilitation. Having the mangrove recovered, the communities set of highly strict local indigenous rules in which every indigenous people who conducting illegal logging in the mangroves would be expelled from the village, while a large fine was given for outside people who did the similar action. Currently, more than 90% of respondents have understood the benefits of mangroves and derived advantages from it, particularly in improving their prosperity and security. The results of the success of mangrove rehabilitation and conservation in SGK was confirmed by the increasing extent of mangrove vegetation using remote sensing data. The case study of rehabilitation and conservation in SGK provided valuable learning for communities in other areas.